Removal of sulfamethoxazole and cephalexin from water by catalytic ozonation process - 509098 Javaid Akhtar; Noraishah Saidina Amin; Azmi Aris, supervisor; Fakulti Kejuruteraan Kimia (2011)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2011